Del Solís a Flor de Maroñas: Ubú de Enrique Permuy y repensando el teatro desde la travesía y la frontera - Remedi, Gustavo (Latin American Theatre Review, 2016)
The 2005 adaptation of Alfred Jarry’s Ubú Rey by Enrique Permuy and Polizonteatro in Flor de Maroñas, a working-class neighborhood in the outskirts of Montevideo, did more than transform the play into a street spectacle. This article explores the connections between the event, which was later replicated in La Teja and other working-class neighborhoods, and a series of poetic and theoretical considerations, including theatre as “journey” and the physical translation of the play to “the border” of Montevideo. This relocation was also a journey to “a cultural frontier,” to the limits and the outside of our lettered, middle-class notions of theatre and theatricality. The author recurs to the notion of “transmodernity” as an alternative to the modern and postmodern aesthetic that predominates within academic circles and renders transmodern theatre invisible. The article also examines the convivial and place-time-specific quality of theatrical productions and the ways in which a long, deep and lively carnivalesque theatrical tradition within working-class neighborhoods makes possible an effective social encounter, exchange, and communication.